FRI0095 SARILUMAB IMPROVED PATIENT-PERCEIVED IMPACT OF RHEUMATOID ARTHRITIS WHATEVER THE BASELINE DISEASE ACTIVITY: FIRST RESULTS FROM AN INTERVENTIONAL NON CONTROLLED STUDY: SARIPRO, IN MODERATE AND SEVERE RHEUMATOID ARTHRITIS PATIENTS. (2nd June 2020) - Gossec, L.; Flipo, R. M.; Schaeverbeke, T.; Albert, C.; Baillet, A.; Boissier, M. C.; Confavreux, C.; Cormier, G.; Dernis, E.; Gervais Solau, E.; Godot, S.; Gottenberg, J. E.; et al.
Abstract : Background: Sarilumab, an anti-IL-6R antibody, is approved for the treatment of moderate to severe RA and shown efficacy on disease activity and patient-reported outcomes (PROs). Detailed analyses of drug efficacy from the patient point of view is important. SariPRO is a pragmatic interventional study close to the daily practice. Objectives: To assess the effectiveness of sarilumab on several PROs using the RAID (Rheumatoid Arthritis Impact of Disease) score. Methods: The SariPRO study (NCT 03449758) was a French multicenter interventional study assessing the effects of sarilumab 200 mg on PROs in patients with moderately to severely active RA with an inadequate response or intolerance to conventional synthetic or biologic DMARDs. The primary endpoint was change in total RAID score from baseline to week 24 (RAID ranges 0-10 where 10 is maximal impact). Changes from baseline for RAID, DAS28-ESR and CDAI according to baseline disease activity were analyzed as secondary outcomes. Safety was assessed by monitoring adverse events (AE). All statistical analyses were descriptive, 95% CI was given when appropriate. Results: 84 patients were included in 31 centers and 62 were evaluable and analyzed for effectiveness. They had similar characteristics to the 84 patients at baseline and were as expected for an RA population initiating a biologic: mean (SD) age: 59.9 (12.4) years, 71.0% female, disease duration 9.7 (10.3) years, rheumatoid factor positivity 82.5%, ACPA positivity 86.4%, and DAS28=4.9 (11). Total RAID score decreased significantly from 5.7 (2.0) at baseline to 3.3 (2.5) at W24; mean change was -2.4 [95% CI: -3.0; -1.8]. Furthermore, this improvement was noted both for highly and less active patients at baseline: for patients with DAS28-ESR < 5.1 (n=31), mean change was -1.56 [-2.28; -0.83] and for patients with DAS28-ESR≥5.1 (n=27), mean change was -1.98 [-2.91; -1.05]. Changes in DAS28-ESR and CDAI were significant (-2.8 [-3.2; -2.4] and -15.2 [-18.5; -11.8], respectively). AEs were consistent with the safety profile of anti-IL-6R antibodies and with results from RCTs (data not shown). Conclusion: In this real world study, treatment with sarilumab during 24 weeks in RA patients led to an improvement in the total RAID score irrespective of baseline levels of disease activity. This is the first time RAID score is used as the primary endpoint in a study. References: [1]Study was sponsored by Sanofi Genzyme Disclosure of Interests: Laure Gossec Grant/research support from: Lilly, Mylan, Pfizer, Sandoz, Consultant of: AbbVie, Amgen, Biogen, Celgene, Janssen, Lilly, Novartis, Pfizer, Sandoz, Sanofi-Aventis, UCB, René-Marc Flipo Consultant of: Johnson and Johnson, MSD France, Novartis, Sanofi, Speakers bureau: Johnson and Johnson, MSD France, Novartis, Sanofi, Thierry Schaeverbeke: None declared, Christine Albert: None declared, Athan Baillet Consultant of: Athan BAILLET has received honorarium fees from Abbvie for his participation as the coordinator of the systematic literature review, marie-Christophe Boissier: None declared, Cyrille Confavreux: None declared, Gregoire CORMIER: None declared, Emmanuelle Dernis Speakers bureau: Lilly, Novartis, Elisabeth Gervais Solau: None declared, Sophie Godot: None declared, Jacques-Eric Gottenberg Grant/research support from: BMS, Pfizer, Consultant of: BMS, Sanofi-Genzyme, UCB, Speakers bureau: Abbvie, Eli Lilly and Co., Roche, Sanofi-Genzyme, UCB, Philippe Goupille Grant/research support from: AbbVie, Amgen, Biogen, BMS, Celgene, Chugai, Lilly, Janssen, Medac, MSD France, Nordic Pharma, Novartis, Pfizer, Sanofi and UCB, Consultant of: AbbVie, Amgen, Biogen, BMS, Celgene, Chugai, Lilly, Janssen, Medac, MSD France, Nordic Pharma, Novartis, Pfizer, Sanofi and UCB, Speakers bureau: AbbVie, Amgen, Biogen, BMS, Celgene, Chugai, Lilly, Janssen, Medac, MSD France, Nordic Pharma, Novartis, Pfizer, Sanofi and UCB, Slim Lassoued: None declared, Thierry Lequerre: None declared, Frederic Lioté Consultant of: CME: Nordic Pharma, Christian Marcelli: None declared, Yves Maugars: None declared, Minh Nguyen: None declared, Aleth Perdriger: None declared, Yves-Marie Pers: None declared, Edouard Pertuiset: None declared, Lucile Poiroux: None declared, Carole Rosenberg: None declared, Christian Roux: None declared, Adeline Ruyssen-Witrand Grant/research support from: Abbvie, Pfizer, Consultant of: Abbvie, BMS, Lilly, Mylan, Novartis, Pfizer, Sandoz, Sanofi-Genzyme, Martin SOUBRIER: None declared, Pascale Vergne-Salle: None declared, Charles Zarnitsky: None declared, Eric Fakra Consultant of: Janssen, Lundbeck, Otsuka, Sanofi, Hubert MAROTTE Grant/research support from: Bristol Myers Sqibb, Lilly France, MSD, Novartis, Nordic Pharma, Pfizer, SanofiAventis, Consultant of: AbbVie, Amgen, Bristol Myers Sqibb, Lilly France, MSD, Novartis, Nordic Pharma, Pfizer, SanofiAventis, Paid instructor for: Sanofi-Aventis, Speakers bureau: Sanofi-Aventis, Florence E Lévy-Weil Employee of: Sanofi Genzyme employee